Magnitude and dosimetric impact of inter-fractional positional variations of the metal port of tissue expanders in postmastectomy patients treated with radiation. (October 2020) - Mayorov, Keren; Ali, Elsayed
Highlights: Inter-fractional port positional errors can be larger than 1.5 cm. Cumulative dosimetric effect of daily measured port errors is minimal. Cumulative dosimetric effect of a systematic registration error can be significant. Assigning the metal port tissue-equivalent density is not an adequate strategy. Alignment of anatomical landmarks should be prioritized over port alignment. Abstract: Background and purpose: Postmastectomy breast reconstruction involves the insertion of a temporary tissue expander, which contains a metal injection port. The purpose of this study was to determine the magnitude and dosimetric impact of the inter-fractional positional variations of the port for patients treated with radiation. Materials and methods: For nine breast cases treated on Tomotherapy, the deviation of the port in the daily MVCT from its reference position was measured in the three cardinal directions. The dosimetric effects of the measured errors were evaluated for two classes of error: Internal Port Error (IPE) and Patient Registration Error (PRE). For each class, dose accumulation was done for daily measured errors and a systematic error. Results: Inter-fractional positional errors of the port were small, with 87% of the deviations below 5 mm, but errors larger than 1.5 cm were observed. The cumulative effect of the daily measured and systematic IPE decreased target coverage by as much as 2.8% and 3.5%, respectively. The cumulative effect of the daily measured PRE decreased target coverage by an average of 3.5%. The cumulative effect of a systematic PRE significantly decreased target coverage by an average of 16%. Conclusion: The presence of IPE over the course of treatment had minimal clinical impact while PRE had a greater impact on clinically-relevant regions. The robustness of treatment delivery can be improved by assigning the port its appropriate density during planning despite contouring uncertainties due to metal artefacts, and by prioritizing anatomical alignment over port alignment during daily registration.